2018
DOI: 10.2134/jeq2017.05.0190
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Soil Organic Carbon Response to Tillage, Yield, and Climate Change in the Southeastern Coastal Plains

Abstract: Intensive tillage, low-residue crops, and a warm, humid climate have contributed to soil organic carbon (SOC) loss in the southeastern Coastal Plains region. Conservation (CnT) tillage and winter cover cropping are current management practices to rebuild SOC; however, there is sparse long-term field data showing how these management practices perform under variable climate conditions. The objectives of this study were to use CQESTR, a process-based C model, to simulate SOC in the top 15 cm of a loamy sand soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 55 publications
1
22
0
Order By: Relevance
“…That does not preclude, however, any more OC storage in the Norfolk topsoil (0−15-cm deep). In fact, recently Nash et al (2018) reported that topsoil SOC increases were projected to occur when our results (2002−2013) were ran through the CQESTR model. The model projected SOC gains of 0.28 Mg C ha −1 upon longer use of CnT, along with corn and cover crops that produce high crop residue returns and belowground OC contributions.…”
Section: Organic Carbon Storage Potentials In Sandy-textured Soilsmentioning
confidence: 76%
“…That does not preclude, however, any more OC storage in the Norfolk topsoil (0−15-cm deep). In fact, recently Nash et al (2018) reported that topsoil SOC increases were projected to occur when our results (2002−2013) were ran through the CQESTR model. The model projected SOC gains of 0.28 Mg C ha −1 upon longer use of CnT, along with corn and cover crops that produce high crop residue returns and belowground OC contributions.…”
Section: Organic Carbon Storage Potentials In Sandy-textured Soilsmentioning
confidence: 76%
“…Findings from these studies identified critical gaps in knowledge. Additional research is needed to: (i) incorporate microbial response to warming and feedback to SOM decomposition into process-based models, (ii) extend SOC measurements and predictions to subsoils, (iii) include saturation algorithms in process-based models to account for topsoil-saturation with C that can occur in some soils (e.g., sandy loam soils under high crop residue inputs in NT; Nash et al, 2018b), (iv) improve climatic projections at smaller scales for different regions, and (v) develop a framework for upscaling SOC stocks to predict influence of biotic and abiotic conditions on SOC stocks at landscape scales. These efforts will assist in further identifying best management practices to enhance SOC stocks and improve the resiliency of agroecosystem and crop production to climate change.…”
Section: Discussionmentioning
confidence: 99%
“…Nash et al (2018b) elucidated the impact of intensive tillage, low‐residue crops, crop yields, and projected climate change on SOC in the top 15 cm of a loamy sand soil under CT or conservation tillage using CQESTR, a process‐based C model, in the southeastern Coastal Plains region in South Carolina. Conservation tillage was predicted to increase SOC by 0.005 to 0.032 Mg C ha −1 yr −1 for six of eight crop rotations compared with CT by 2033.…”
Section: Process‐based Models To Evaluate Soil Organic Carbon Dynamicsmentioning
confidence: 99%
“…Cover crops take up P derived from the decomposition of SOC and crop residues and return P back to soils in the forms of residues (Figure 4). Although cover crop biomass production was not available for these plots, the production of a similar mixture in adjacent fields (<1 km) resulted in estimated 6-8 kg ha −1 of residue Po into soils annually (Nash et al, 2018;Ye et al, 2019). However, the observed increased Po stock can be also attributable to the possibility that cover cropping reduced the losses of labile Po from the top soil by leaching or surface runoff (Djodjic et al, 2006;King et al, 2015).…”
Section: Cover Cropping and P Fractionsmentioning
confidence: 99%
“…Winter cover crop mixtures (i.e., cereal rye [Secale L.] and crimson clover [Trifolium incarnatum L.]) were introduced to the experiment in 2015 as a split-plot in winter fallow plots. Additional site description, crop rotation, and management practice details can be found in relevant studies (Hunt et al, 1997;Karlen, Hunt, & Campbell, 1984;Nash et al, 2018;Novak, Bauer, & Hunt, 2007). The current experiment consisted of the following four treatments: (a) conservation tillage with cover crops (CS-Cover); (b) conservation tillage without cover crops (CS-Fallow); (c) conventional tillage with cover crops (CV-Cover); and (d) conventional tillage without cover crops (CV-Fallow).…”
Section: Introductionmentioning
confidence: 99%